Post a New Question

Math

posted by .

h(x)=(2-2x^2)/-2
h(-2)

I get (-2-2(-2)^2)/-2
(-2-2(4)/-2
6/-2=-3

h(-2)=-3

  • Math -

    h(x) = (2 - 2x^2)/-2

    h(-2) = (2 - 2[2^2])/-2
    h(-2) = (2 - 2[4])/-2
    h(-2) = (2 - 8)/-2
    h(-2) = -6/-2
    h(-2) = 3

    This is what I get from what the original function was as typed and plugging -2 into it.

  • Math -

    I see what I did, I put a neg in front when it should have been and carried it through. Thanks

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question